Polymorphism of the IL-8 gene and the risk of ovarian cancer. Issue 2 (February 2015) - Koensgen, D.; Bruennert, D.; Ungureanu, S.; Sofroni, D.; Braicu, E.I.; Sehouli, J.; Sümnig, A.; Delogu, S.; Zygmunt, M.; Goyal, P.; Evert, M.; Olek, S.; et al.
Highlights Four single nucleotide polymorphisms (SNPs) of the IL-8 gene were analyzed. 268 Ovarian cancer (OC) patients and 426 healthy women were included in this study. OC patients from three European hospitals were screened. IL-8 +781 C/T and IL-8 +2767 A/T SNPs show significant association with higher risk of OC.